Low maintenance turf – quality and weed aspects. - Żurek, Grzegorz; Tomaszewski, Bartosz (Plant Breeding and Seed Science, 2009)
Turfgrass varieties of Festuca rubra ssp. rubra, F.r. ssp. trichophylla, F. nigrescens, F.arundinacea, F.ovina ssp. vulgaris, F.o. ssp duriuscula, Lolium perenne and Poa pratensis as well as mixtures of high and low share of Lolium perenne were tested in low maintenance conditions during 5 years and evaluated for: shoot density, visual merit and for weed infestation. None of tested entries was able to keep initial quality. Only for few of them (mostly varieties of Festuca ovina ssp. duriuscula and F.arundinacea) visual merit after 5 years was still close to the level of minimal user-accepted value (5 in 1-9 scale). The least visual merit values were noted for Poa pratensis and Festuca rubra ssp. rubra...